Perancangan Sistem Informasi (SIMEEPORT) Berbasis Web - Fernando Siahaan; Rizka Aisyah Hasibuan; Siti Nurhasanah; Felix Wuryo Handoko; Syaiful Anwar (Jurnal INSAN: Journal of Information System Management Innovation, 2022)
The scheduling system in the use of the room is needed in order to support the work of the organization, the scheduling at PT Dargo Kreatifindo Digital is still manual so it takes a long time and causes errors in data collection. A web-based information system is needed in handling this scheduling system. The system development model used is the waterfall model with five stages, namely system requirements analysis, system design as a web-based system blueprint, coding, black box testing and system maintenance. The research results from use case diagrams, activity diagram designs, sequence diagrams, system designs and system testing. In conclusion, this website-based scheduling system makes it easier for staff to arrange room scheduling easily and quickly to find out the latest space usage, making it easier to convey information on room utilization.